1997
DOI: 10.4049/jimmunol.158.1.501
|View full text |Cite
|
Sign up to set email alerts
|

The state of maturation of monocytes into macrophages determines the effects of IL-4 and IL-13 on HIV replication.

Abstract: The molecular mechanisms of the effects of IL-4 and IL-13 on HIV infection in human monocytes as they matured into monocyte-derived macrophages over 7 days were investigated using HIV-1(BaL), and low passage clinical strains. IL-4 and IL-13 up-regulated the expression of both genomic and spliced HIV mRNA in monocytes cultured on Teflon, as determined by Northern analysis and p24 Ag assay. Using a nuclear run-on assay, IL-4 stimulation was shown to enhance transcription by two- to threefold. IL-4 stimulated nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study showed that IL-4 stimulation enhanced transcription that is mediated by IL-4 stimulated NF-κB nuclear translocation. Further, they also state that IL-4 and IL-13 inhibited HIV replication at the transcriptional level in monocyte-derived macrophages after 3 to 5 days of adherence to the surface of plastic culture plates ( 49 ). Interestingly, it has been observed that IL-4 favored the replication of T-tropic (X4) virus as compared to M-tropic (R5) replication ( 50 ), favoring X4 virus generation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that IL-4 stimulation enhanced transcription that is mediated by IL-4 stimulated NF-κB nuclear translocation. Further, they also state that IL-4 and IL-13 inhibited HIV replication at the transcriptional level in monocyte-derived macrophages after 3 to 5 days of adherence to the surface of plastic culture plates ( 49 ). Interestingly, it has been observed that IL-4 favored the replication of T-tropic (X4) virus as compared to M-tropic (R5) replication ( 50 ), favoring X4 virus generation.…”
Section: Discussionmentioning
confidence: 99%